Using the Opportunities of Telepedagogy in Forming a Culture of International Communication in Students (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article discusses the use of educational, educational, and motivational possibilities of telepedagogy in the formation of the culture of interethnic communication among future teachers. Pedagogical conditions for the development of knowledge, skills, and abilities related to this field, as well as the directions of telepedagogy, are given. Pedagogical opportunities related to the presentation of formal, informal, and referential information and which pedagogical methods are used by future teachers for the successful assimilation of television information by students were analyzed.